lslamic Orthodoxy and Hegemonic Power: A Comparative Study of Indonesia and the Abbasid Dynasty through Antonio Gramsci’s Perspective - Aby Isnain Naafie Waasinas; Fadil Sj (Politea : Jurnal Politik Islam, 2026)
This study examines the political hegemony of Islamic orthodoxy in the Abbasid Dynasty and Nahdlatul Ulama (NU) through a comparative analysis using Antonio Gramsci’s theory of hegemony. The research aims to analyze how religious orthodoxy is constructed through the interaction of political legitimacy, religious authority, and the production of discourse, as well as how these mechanisms shape the position of theological groups outside the mainstream. Employing a library research method with comparative, historical, and conceptual approaches, this study finds that the Abbasid Dynasty relied primarily on state power and official orthodoxy during the Mihnah to establish theological authority, whereas NU has developed religious orthodoxy through civil society networks, including pesantren, educational institutions, da‘wah activities, and political engagement. Despite these differences, both cases demonstrate that the sustainability of orthodoxy depends not only on formal political authority but also on the ability to generate social consensus and legitimacy. The findings indicate that the political hegemony of Islamic orthodoxy plays a significant role in defining the boundaries of religious legitimacy and the acceptability of theological groups within Muslim societies.